Robotic-assisted mitral valve surgery without aortic cross-clamping: a safe and feasible technique - Ökten, Eyüp Murat; Özcan, Zeynep Sıla; Arslanhan, Gökhan; Şenay, Şahin; Güllü, Ahmet Ümit; Koçyiğit, Muharrem; Değirmencioğlu, Aleks; Alhan, Cem (Frontiers in Cardiovascular Medicine, 2023)
Background The primary objective of this study was to evaluate the safety and feasibility of robotic-assisted mitral valve surgery without aortic cross-clamping. Methods From January 2010 to September 2022, 28 patients underwent robotic-assisted mitral valve surgery without aortic cross-clamping in our center using DaVinci Robotic Systems. Clinical data during the perioperative period and early outcomes of the patients were recorded. Results Most patients were in New York Heart Association (NYHA) class II and III. Mean age and EuroScore II of the patients were 71.5 ± 13.5 and 8.4 ± 3.7 respectively. The patients underwent either mitral valve replacement (n = 16, 57.1%) or mitral valve repair (n = 12, 42.9%). Concomitant procedures were performed including tricuspid valve repair, tricuspid valve replacement, PFO closure, left atrial appendage ligation, left atrial appendage thrombectomy and cryoablation for atrial fibrillation. Mean CPB times were 140.9 ± 44.6 and mean fibrillatory arrest duration was 76.6 ± 18.4. Mean duration of ICU stay was 32.5 ± 28.8 h and mean duration of hospital stay 9.8 ± 8.3 days. One patient (3.6%) underwent revision due to bleeding. New onset renal failure was observed in one (3.6%) patient and postoperative stroke in one (3.6%) patient. Postoperative early mortality was observed in two (7.1%) patients. Conclusions Robotic-assisted mitral valve surgery without cross-clamping is a safe and feasible technique in high-risk patients undergoing redo mitral surgery with severe adhesions as well as in primary mitral valve cases that are complicated with ascending aortic calcification.